PELATIHAN MULTIMEDIA UNTUK KARYAWAN DAN ANGGOTA TNI DI PUSINFOLATHA - wo2ntea Wowon Priatna; M. Fadhli Nursal; Tyastuti Sri Lestari; Joni Warta (Fakultas Ekonomi Dan Bisnis Universitas Bhayangkara Jakarta Raya, 2021)
The purpose of this multimedia is to improve the ability of training members and employees with abilities in the field of multimedia through. Multimedia uses several media to present information which is a combination of text, graphics, animation, images, video and sound such as making graphic designs, text, images, video, audio, animation. This implementation was carried out for 2 months starting from the training in July and August 2019 at the Pushinfolatha Computer Lab, TNI Headquarters, Cilangkap. The training participants are TNI members and PNS employees and 20 people. The training was carried out using practical methods in the Pusinfolatha computer lab with the material presented was making infographic-based presentations, making logos, posters, banners, banners and video editing. The implementation of this training was successful and all participants were able to follow the training material well, it can be seen from the work and evaluation results that the average score obtained by participants was above 90.